The Effects of Middle School Physical Education Curriculum on Student Attitudes: 美國中學生對體育課程的態度 - David BARNEY, David; Joe DEUTSCH, Joe (Asian Journal of Physical Education & Recreation, 2009)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. Middle school physical education can serve as an important tool in shaping students opinions and behaviors regarding lifelong physical activity. The curriculum in middle school physical education is one component that can positively or negatively affect a students’ attitude toward physical activity throughout their life. The purpose of this study was to investigate the middle school physical education curriculum and its effect on middle school students’ attitudes and perceptions towards their physical education class. It was found that middle school students do like the curriculum they participate in, mainly consisting of team sports. 中學體育在塑造學生的觀點和行為，可能擔當一個關於終身體育活動的重要工具。中學體育課程能夠正面地或間接地影響學生對體育活動的態度，以及他們日常生活行為的一個組分。本項研究的目的將調查中學體育課程及它的作用，如何影響中學生的日常行為及對體育的態度。結果中學生整體上喜歡體育課程，尤其是隊際體育項目。